Abstract Book of The 8th International Conference on Nanomaterials and Advanced Energy Storage Systems - (:unkn) unknown (The 8th International Conference on Nanomaterials and Advanced Energy Storage Systems; Nazarbayev University; National Laboratory Astana; Institute of Batteries, 2020)
The INESS 2020 topics covered the following and related areas: advanced nanomaterials for energy application, advanced energy storage, conversion and saving systems, materials for electrochemical sensor and electroanalytical applications, catalysis and fuel cells, battery monitoring and management systems, battery safety and utilization, development of electric vehicles and stationary energy storage. The scientists and students from Japan, Korea, France, Germany, China, Russia, Canada, UAE, UK, Turkey and Kazakhstan reviewed and discussed the recent progress and problems in materials science, nanotechnologies, ecology, renewable energy, energy storage systems and modeling methods in these fields.
Keywords: Research Subject Categories::TECHNOLOGY; Research Subject Categories::TECHNOLOGY::Other technology; battery capacity problem; Smart energy systems; Energy and environment; Battery safety and utilization; Advanced Nanomaterials